2015
DOI: 10.1523/jneurosci.2454-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Attenuation of Mnemonic Rule Representation in Macaque Dorsolateral Prefrontal Cortex during a Pro- and Anti-Saccade Task

Abstract: Maintenance of context is necessary for execution of appropriate responses to diverse environmental stimuli. The dorsolateral prefrontal cortex (DLPFC) plays a pivotal role in executive function, including working memory and representation of abstract rules. DLPFC activity is modulated by the ascending cholinergic system through nicotinic and muscarinic receptors. Although muscarinic receptors have been implicated in executive performance and gating of synaptic signals, their effect on local primate DLPFC neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 95 publications
(11 reference statements)
6
36
2
Order By: Relevance
“…However, it is still possible that baseline ACh levels differ strongly between anesthetized and awake animals, and thus switches from facilitation to inhibition occur at different application levels. Despite this, the overwhelming number of studies reported that ACh application results on increased activity in V1 (Sillito and Kemp, 1983 ; Sillito et al, 1985 ; Sato et al, 1987 ; Roberts et al, 2005 ; Zinke et al, 2006 ; Herrero et al, 2008 ; Goard and Dan, 2009 ; Kuo et al, 2009 ; Rodriguez et al, 2010 ; Soma et al, 2012 , 2013 ; Pinto et al, 2013 ), and in other cortical areas (McKenna et al, 1988 ; Metherate et al, 1988a , b ; Matsumura et al, 1990 ; Tremblay et al, 1990 ; Bhattacharyya et al, 2012 , 2013 ; Thiele et al, 2012 ; Yang et al, 2013 ; Major et al, 2015 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still possible that baseline ACh levels differ strongly between anesthetized and awake animals, and thus switches from facilitation to inhibition occur at different application levels. Despite this, the overwhelming number of studies reported that ACh application results on increased activity in V1 (Sillito and Kemp, 1983 ; Sillito et al, 1985 ; Sato et al, 1987 ; Roberts et al, 2005 ; Zinke et al, 2006 ; Herrero et al, 2008 ; Goard and Dan, 2009 ; Kuo et al, 2009 ; Rodriguez et al, 2010 ; Soma et al, 2012 , 2013 ; Pinto et al, 2013 ), and in other cortical areas (McKenna et al, 1988 ; Metherate et al, 1988a , b ; Matsumura et al, 1990 ; Tremblay et al, 1990 ; Bhattacharyya et al, 2012 , 2013 ; Thiele et al, 2012 ; Yang et al, 2013 ; Major et al, 2015 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking dopamine receptor D1, for instance, revealed an "inverted U" dose-response relationship because too little or too much receptor activity reduces persistent firing (Vijayraghavan et al, 2007), and both D1 and D2 receptors influence the representation of task rules during a delay (Ott et al, 2014). Similarly, acetylcholine has been implicated in the maintenance of persistent activity through its action on nicotinic (Yang et al, 2013;Sun et al, 2017) and muscarinic receptors (Krnjevic et al, 1971;Andrade, 1991;Egorov et al, 2002), although a recent study demonstrated that the decrease in activity caused by muscarinic blockers is not specific to delay activity (Major et al, 2015), just as we observed for NMDARs. Furthermore, a2A-adrenoceptors (Li et al, 1999; also impact on persistent firing, in part by acting on nonselective cation-permeable transient receptor potential channels (TRP channels) (Yan et al, 2009) and hyperpolarization activated cyclic nucleotide-gated potassium channels (M. Wang et al, 2007;Thuault et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most of our understanding of the physiological consequences of PFC neuromodulation has been accrued from microiontophoretic, local and systemic injection studies in the PFC of monkeys performing the oculomotor delayed response task. Recently, several groups have begun to explore the role of dopamine in other PFC-dependent functions, including top-down attention (Noudoost and Moore, 2011a ; Soltani et al, 2013 ), visuomotor associative learning (Puig and Miller, 2012 ) and WM for abstract rules in numerical cognition and controlled oculomotor behavior (Jacob et al, 2013 ; Ott et al, 2014 ; Major et al, 2015 ; Vijayraghavan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%